In vitro and in vivo evaluation of electrochemotherapy with trans-platinum analogue trans-PtCl2(3-Hmpy)2 - Kranjc, Simona (Radiology and oncology (Ljubljana), 2017)
Background. Cisplatin is used in cancer therapy, but its side effects and acquired resistance to cisplatin have led to the synthesis and evaluation of new platinum compounds. Recently, the synthesized platinum compound trans- PtCl2(3-Hmpy)2 (3-Hmpy = 3-hydroxymethylpyridine) (compound 2) showed a considerable cytotoxic and antitumour effectiveness. To improve compound 2 cytotoxicity in vitro and antitumour effectiveness in vivo, electroporation was used as drug delivery approach to increase membrane permeability (electrochemotherapy). Materials and methods. In vitro, survival of sarcoma cells with different intrinsic sensitivity to cisplatin (TBLCl2 sensitive, TBLCl2Pt resistant and SA-1 moderately sensitive) was determined using a clonogenic assay after treatment with compound 2 or cisplatin electrochemotherapy. In vivo, the antitumour effectiveness of electrochemotherapy with compound 2 or cisplatin was evaluated using a tumour growth delay assay. In addition, platinum in the serum, tumours and platinum bound to the DNA in the cells were performed using inductively coupled plasma mass spectrometry. Results. In vitro, cell survival after treatment with compound 2 electrochemotherapy was significantly decreased in all tested sarcoma cells with different intrinsic sensitivity to cisplatin (TBLCl2 sensitive, TBLCl2Pt resistant and SA-1 moderately sensitive). However, this effect was less pronounced compared to cisplatin. Interestingly, the enhancement factor (5-fold) of compound 2 cytotoxicity was equal in cisplatin-sensitive TBLCl2 and cisplatin-resistant TBLCl2Pt cells. In vivo, the growth delay of subcutaneous tumours after treatment with compound 2 electrochemotherapy was lower compared to cisplatin. The highest antitumour effectiveness after cisplatin or compound 2 electrochemotherapy was obtained in TBLCl2 tumours, resulting in 67% and 11% of tumour cures, respectively. Compound 2 induced significantly smaller loss of animal body weight compared to cisplatin. Furthermore, platinum amounts in tumours after compound 2 or cisplatin electrochemotherapy were approximately 2-fold higher compared to the drug treatment only, and the same increase of platinum bound to DNA was observed. Conclusions. The obtained results in vitro and in vivo suggest compound 2 as a potential antitumour agent in electrochemotherapy.
Keywords: 3-Hmpy; analog platine; cisplatin; electrochemotherapy; elektrokemoterapija; elektroporacija; elektroporation; platinum analogue